Surgical and Patient-Reported Outcomes of Open Perforator-Preserving Anterior Component Separation for Ventral Hernia Repair - Bustos, Samyd S.; Kuruoglu, Doga; Truty, Mark J.; Sharaf, Basel A. (Journal of Reconstructive Microsurgery, 2023)
Background Abdominal wall reconstruction is challenging for surgeons and may be life altering for patients. There are scant high-quality studies on patient-reported outcomes following abdominal wall reconstruction. We assess long-term surgical and patient-reported outcomes of perforator-preserving open anterior component separation (OPP-ACS) following large ventral hernia repair.Methods A retrospective review of patients with large ventral hernia defects who underwent OPP-ACS performed by the authors (B.A.S., M.J.T.) was conducted between 2015 and 2019. Demographics, surgical history, operative details, outcomes, and complications were extracted. A validated questionnaire, Carolinas Comfort Scale (CCS), was used to assess postoperative quality of life.Results Twenty-two patients (12 males and 10 females) with a mean age and BMI of 60.9 ± 10 years and 28.9 ± 4.8 kg/m2, respectively, were included. Mean follow-up was 28.5 ± 16.3 months. All had prior abdominal surgery; 15 (68%) for abdominopelvic malignancy, 3 (14%) for previous failed hernia repair, and 8 (36%) had history of abdominopelvic radiation. Overall, 16 (73%) hernias were in the midline, 4 (18%) in the right lower quadrant, 1 (4.5%) in the right upper quadrant, and 1 (4.5%) in the left lower quadrant. Mean hernia defect surface area was 145 ± 112 cm2. A total of 9 patients (40.9%) underwent bilateral component separation, whereas 13 (59.1%) had unilateral. Bioprosthetic mesh was used in all patients as underlay. Mean mesh size and thickness were 545.6 ± 207.7 cm2 and 3.4 ± 0.5 mm, respectively. One patient presented with a minor wound dehiscence, and two presented with seromas not requiring aspiration/evacuation. One patient had hernia recurrence 22 months after surgery. One patient was readmitted for partial small bowel obstruction and one required wound revision. A total of 14 (65%) patients responded to the CCS questionnaire. At 12 months, mean score for all 23 items was 0.29 ± 0.21 (0.08–0.62), which corresponds to absence or minimal symptoms.Conclusion The OPP-ACS is a safe surgical option for large, complex ventral hernias. Our cases showed minimal complication rate and hernia recurrence, and our patients reported significant improvement in life quality.
Keywords: ventral hernia; component separation; perforator